With all reservations: essays’s aesthetics and ethics (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This paper introduces the idea that essay has a aesthetics, a literary style, but at the same time this aesthetics is a mental style that presupposes a ethics as ground. Therefore, we think the essay as philosophy. More precisely: in modernity, philosophy is essayistic. This essay’s philosophy has five main characteristics that are inseparable from each other. Essay is based on life-world and in consequence is a experimental philosophy opposed to the rationalist system. This philosophy is a philosophy of finitude, anti-absolutist, that defends the philosophical relevance of the concrete and real subject. Finally, the essay understands critical reflection as a method of freedom. Essayistic philosophy contains a ethics that avoids both rationalist totalitarianism and aestheticist nihilism, and that concludes in a dialogical pluralism
Keywords: Essay; Philosophy; Aesthetics; Ethics; anti-absolutism; pluralism